Natural molecule coatings modify the fate of cerium dioxide nanoparticles in water and their ecotoxicity to Daphnia magna. (February 2020) - Villa, Sara; Maggioni, Daniela; Hamza, Hady; Di Nica, Valeria; Magni, Stefano; Morosetti, Bianca; Parenti, Camilla Carla; Finizio, Antonio; Binelli, Andrea; Della Torre, Camilla
Abstract: The ongoing development of nanotechnology has raised concerns regarding the potential risk of nanoparticles (NPs) to the environment, particularly aquatic ecosystems. A relevant aspect that drives NP toxicity is represented by the abiotic and biotic processes occurring in natural matrices that modify NP properties, ultimately affecting their interactions with biological targets. Therefore, the objective of this study was to perform an ecotoxicological evaluation of CeO2 NPs with different surface modifications representative of NP bio-interactions with molecules naturally occurring in the water environment, to identify the role of biomolecule coatings on nanoceria toxicity to aquatic organisms. Ad hoc synthesis of CeO2 NPs with different coating agents, such as Alginate and Chitosan, was performed. The ecotoxicity of the coated CeO2 NPs was assessed on the marine bacteria Aliivibrio fischeri, through the Microtox® assay, and with the freshwater crustacean Daphnia magna. Daphnids at the age of 8 days were exposed for 48 h, and several toxicity endpoints were evaluated, from the molecular level to the entire organism. Specifically, we applied a suite of biomarkers of oxidative stress and neurotoxicity and assessed the effects on behaviour through the evaluation of swimming performance. The different coatings affected the hydrodynamic behaviour and colloidal stability of the CeO2 NPs in exposure media. In tap water, NPs coated with Chitosan derivative were more stable, while the coating with Alginate enhanced the aggregation and sedimentation rate. The coatings also significantly influenced the toxic effects of CeO2 NPs. Specifically, in D. magna the CeO2 NPs coated with Alginate triggered oxidative stress, while behavioural assays showed that CeO2 NPs coated with Chitosan induced hyperactivity. Our findings emphasize the role of environmental modification in determining the NP effects on aquatic organisms. Graphical abstract: Image 1 Highlights: CeO2 NPs were coated with Alginate and Chitosan and their ecotoxicity was assessed. The coating with natural molecules modified the stability and hydrodynamic behaviour of CeO2 NPs. Natural coating conferred new ecotoxicological properties towards Daphnia magna . The interaction between NPs and natural molecules is a driver of NPs' ecotoxicity. Abstract : Interactions with environmental molecules influence the fate and ecotoxicity of NPs.